Effect of good meeting practices and interactional justice on online workplace informal learning in Korea - Kim, Minjung; Park, Min Jae (Information Development, 2022)
The purpose of this study is to investigate the contextual factors that facilitate informal workplace learning during the meeting process or after the meeting in the online context. This research utilized structural equation modeling technique and the target sample of this study was fulltime workers employed at various levels within a wide range of organizations. The results show that good meeting practice has a positive impact on external scanning among the three types of informal learning. Specifically, good meeting practice is not significantly related to learning with others and self-experimentation but is positively associated with external scanning. Interactional justice, which is comprised of interactional and informational justice, has a significant effect on learning with others and the self-experimentation learning type Neither interactional nor informational justice is significantly related to external scanning. Furthermore, the moderating effects of the relationship among good meeting practices, interactional justice and informal learning are based on demographic profiles, especially gender. The findings are distinctively different in terms of several hypotheses depending on gender.
Keywords: gender; good meeting practice; informal learning; interactional justice; online learning